Enhancing Anticoagulation Continuing Professional Development with Experiential Learning - Jeff Nagge; Sherilyn Houle; Marie Lippens; Cynthia Richard; Rosemary Killeen; Brianna Bennett; Annik Bilodeau (Journal of Innovation in Polytechnic Education)
Objective: This study aims to determine the value of including practical experiential learning in a continuing professional development (CPD) course primarily for pharmacists. The Management of Oral Anticoagulation Therapy (MOAT) course blends self-paced online learning with experiential training in an anticoagulation clinic under expert supervision.